1996
DOI: 10.1021/om9601864
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolyl-Bridged Iridium Dimers. 16.1 The Atropisomeric (C2) System [Ir(CO)(PPh3)(μ-pz)]2. Synthesis of Homologous Diastereomeric Complexes That Undergo Slow Stereomutation by Ring Inversion of the Bridging Framework:  Mechanistic Implications for Bimetallic Substrate Activation

Abstract: The diiridium(I) complex [Ir(P{OR*}Ph 2 )-(CO)(µ-pz)] 2 (R* ) Bor, 4a,b, OBor ) (1S)-endo-(-)bornoxy) exists as two diastereomers (63:37 ratio, 1 H and 31 P NMR) that are found to cocrystallize, providing a source of 4a,b in nonequilibrium distribution. NMR measurements show that MeI adduct formation to give the diastereomeric pair of diiridium(II) adducts 7a,b is orders of magnitude faster than ring inversion that interconverts 4a and 4b and that 7a,b equilibrate much more slowly than the 4a-4b interconversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Binuclear transition-metal complexes based on Pt(II) have also generated profound interest because of their intriguing photophysical properties. , In particular, the rich excited-state chemistry of the binuclear [Pt 2 (μ-P 2 O 5 H 2 ) 4 ] 4– has been reported in the literature, while there are numerous related chromophores that display changes in their photophysical properties with variation of ancillary and charge transfer ligands. , In addition to Pt, there have been several reported studies on binuclear complexes of Pd and Ir. In select binuclear Pt(II) complexes, the d z 2 orbital of each platinum center is forced to σ overlap and this interaction gives rise to filled dσ and dσ* orbitals. This electronic structure effectively transforms high-energy absorbing mononuclear structures into colorful dinuclear molecules exhibiting reversible metal–metal-based oxidations with riveting photophysics. When the metal–metal coupling is sufficient, the photophysical properties can be considered to result from metal–metal-to-ligand charge transfer (MMLCT) excited states, involving charge transfer between a filled Pt–Pt dσ* orbital and a ligand-localized vacant π*orbital on the cyclometalating ligand (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Binuclear transition-metal complexes based on Pt(II) have also generated profound interest because of their intriguing photophysical properties. , In particular, the rich excited-state chemistry of the binuclear [Pt 2 (μ-P 2 O 5 H 2 ) 4 ] 4– has been reported in the literature, while there are numerous related chromophores that display changes in their photophysical properties with variation of ancillary and charge transfer ligands. , In addition to Pt, there have been several reported studies on binuclear complexes of Pd and Ir. In select binuclear Pt(II) complexes, the d z 2 orbital of each platinum center is forced to σ overlap and this interaction gives rise to filled dσ and dσ* orbitals. This electronic structure effectively transforms high-energy absorbing mononuclear structures into colorful dinuclear molecules exhibiting reversible metal–metal-based oxidations with riveting photophysics. When the metal–metal coupling is sufficient, the photophysical properties can be considered to result from metal–metal-to-ligand charge transfer (MMLCT) excited states, involving charge transfer between a filled Pt–Pt dσ* orbital and a ligand-localized vacant π*orbital on the cyclometalating ligand (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…We now present new trinuclear gold complexes displaying interesting mesomorphic properties prepared from nonmesogenic pyrazolate ligands. The choice of these ligands is based on the well-known ability of azolates to yield di-, tri-, tetra-, hexa-, or octanuclear complexes containing metal centers, such as rhodium, iridium, copper, , silver, or gold, , joined by one or two exobidentate ligands . Additionally, with the exception of a related work on mesogenic pyrazaboles, pyrazolate-based molecules have not been used as organic ligands to generate mesogenic complexes.…”
Section: Introductionmentioning
confidence: 99%
“…E. X-ray Crystallography. All procedures conformed to those adopted earlier. ,, Additional details, including metric parameters, are included in the Supporting Information. Crystal data for compounds 2 − 4 , 6 , and 7 are collected in Table .…”
Section: Methodsmentioning
confidence: 99%
“…It is in this domain that the d 7 +2 state has emerged as an important conjunction in the chemistry of iridium. Thus, in particular, it has been shown that d 7 2 complexes (Ir II −Ir II ) can function as stable termini to oxidative steps using binuclear d 8 2 prototypes; can exist in equilibrium with the latter; or can be accessed reductively from oxidized d 6 2 analogues . It is striking, therefore, that although concerted addition of dihydrogen to a mononuclear metal center (including, conspicuously, d 8 Ir I ) is a familiar event, only a handful of reports exist of iridium dimers reacting similarly. Direct uptake of molecular hydrogen by any neutral homobinuclear transition-metal complex has in fact remained distinguished by its rarity, although such addition to a mixed-valence (Ir 0 −Ir II , i.e., d 9 −d 7 ) diiridium core, together with the demonstration that parahydrogen-induced polarization (PHIP) can be used to characterize its stereochemical profile, are two very recent and exciting developments in this context.…”
Section: Introductionmentioning
confidence: 99%